La patrimonialisation de la pédagogie de la création artistique, entre schéma heuristique et interactions institutionnelles - Stéphanie-Emmanuelle Louis (In Situ)
The « History of the pedagogy of artistic creation » program relies on an inventory of sources related to the history of five art schools located in Paris, including the ENSAD and the ENSBA. Research seems to play an important emulation role in the heritage designation process, but also to reveal the different patrimonial dimensions of objects. This is particularly apparent in the case of the valuing of the ENSAD’s audio-visual archives fonds. Beyond a collection of supports, this is a collection of actions and interactions between teachers and students, which opens new perspectives for the historiography of the pedagogy of creation.